Komposisi Efektif Batok Kelapa sebagai Karbon Aktif untuk Meningkatkan Kualitas Airtanah di Kawasan Perkotaan - Salim, Noor; Rizal, Nanang Saiful; Vihantara, Ricky (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Shallow groundwater in urban areas today is no longer fully utilized directly for domestic human needs. Some of the factors that cause, among others, due to pollution of springs by household waste, too much groundwater production resulting in the reduced amount of ground water. Finally the water function as a solvent and the neutralizer of the pollutant decreases as the water becomes less clear. By utilizing coconut shells as activated carbon mixed with silica sand, zeolite, and manganesee in this research can reduce turbidity, TDS and ground water PH so that the water produced can meet clean water standards according to PERMENKES/RI No.416/IX/1990. The objective of this study was to find an effective mixture composition to purify water using 5 different mixing compositions and it can be concluded in this study that coconut shells used as activated carbon amount to 35% of total media composition. So the most optimal composition to produce water with good quality of 35% active carbon, 25% silica sand, manganese 20%, 20% zeolite. In this composition also, Mangan (Mn) and Iron (Fe) have decreased and meet the quality standard of raw water quality as required by PERMENKES quality standard of Class B water quality.